Modifikasi Cadangan Premi Tahunan Retrospektif Pada Asuransi Jiwa Berjangka Kasus Joint Life Dengan Metode Zillmer - Ihsan Kamil; Suherman Suherman; Dewi Murni (UNIVERSITAS NEGERI PADANG, 2021)
Abstract – Insurance company in carrying out its duties requires a fee. It causes the values of premiums paid by the policy participants increase. Premiums which involve additional costs are named gross premiums. Most of the premiums paid are a premium reserves which should be provided by the insurance company as a liability if there is a claim in the future. In this research, the value of the reserves was calculated with retrospective method which is modified with Zillmer method for life term insurance product case joint life, where two people just pay one insurance policy. In the calculation of Zillmer reserve, gross premiums used as the basis of calculation. Furthermore, interest rates also affect the value of reserves and the value of premium that must be paid by the participants. The mortality tables used is Table Mortality Indonesia (TMI) 2011. Keywords – Premium Reserves, Zillmer Method, Retrospective, Life Insurance, Joint Life